A physically based rheological model for predicting the flow behavior of non-newtonian crude oil mixtures under cold climate conditions - Nikolaev, Alexander; Goluntsov, Andrey; Plotnikova, Kristina (Frontiers in Chemical Engineering, 2026)
Accurate prediction of the rheological behavior of heavy crude oil mixtures is essential for pipeline transport under cold climate conditions. This study presents a physically based non-Newtonian rheological model that incorporates the coupled effects of temperature and mixture composition through temperature- and concentration-dependent expressions for the consistency coefficient and flow behavior index. The model was calibrated and validated using 88 experimental rheological measurements on binary mixtures of heavy Severo-Komsomolskoye and light Vankor crudes over a temperature range of 5C–60 °C, heavy-oil concentrations of 0%–100%, and shear rates of 1–300 s-1. The proposed model predicts shear stress with a mean relative deviation of 8.7% and a root mean square error below 0.95 Pa, outperforming conventional Arrhenius, Refutas, and classical power-law correlations by a factor of 2–3. The model accurately captures the transition from non-Newtonian to near-Newtonian behavior with increasing temperature and dilution, providing a practical tool for hydraulic calculations and flow assurance design in cold-region pipeline systems.